A reverse-type sandwich enzyme-linked immunosorbent assay for detecting antibodies to Borna disease virus. - Horimoto, T (1997)
To investigate whether there is an epidemiological correlation between Borna disease virus (BDV) infection and human neuropsychiatric diseases, we established a reverse-type sandwich enzyme-linked immunosorbent assay (RS-ELISA) for detecting specific antibodies to BDV. In this assay, microplate wells were coated dispersely with BDV p40 antigen, followed by the addition of test samples at a low dilution and then the biotinylated p40. A preformed complex of streptavidin and horseradish peroxidase-conjugated biotin and an enzyme substrate were used to measure the captured biotinylated p40. Theoretically, RS-ELISA should specifically detect anti-BDV antibodies without nonspecific signals; such signals possibly occur in conventional serological assays. Additionally, the RS-ELISA could be applied under the same protocols to test samples from a variety of animals. By using anti-BDV rat and rabbit sera, the assay was standardized so that it had high specificity and sensitivity. When we used the RS-ELISA to determine the presence of anti-BDV antibodies in plasma from 70 patients with chronic schizophrenia as well as 40 healthy individuals in the Tokyo area of Japan, no plasma sample was found to possess specific antibodies to BDV p40, indicating no association between BDV infection and the disease in our testing population. A negative reaction was also shown for the sera that had previously been judged to be seropositive for BDV by an immunofluorescence or immunoblot test. These findings suggested that false-positive cases of infection due to nonspecific reactions may be included in previous seroepidemiological information with regard to BDV.